Does fixed retention prevent overeruption of unopposed mandibular second molars in maxillary first molar extraction cases? - Christos Livas; Demetrios J. Halazonetis; Johan W. Booij; Christos Katsaros; Yijin Ren (SpringerOpen, 2016)
Abstract Background The objective of this study was to investigate whether multistranded fixed retainers prevented overeruption of unopposed mandibular second molars in maxillary first molar extraction cases. Methods The panoramic radiographs of 65 Class II Division 1 Caucasian Whites (28 females, 37 males) consecutively treated with bilateral maxillary first molar extraction and the Begg technique, and with records taken after treatment (T1) and in retention (T2), were withdrawn from private practice records. After appliance removal, mandibular second molars were retained with sectional wires till at least T2 in case of lack of occlusal contact with the antagonist. The subjects were assigned to study-retention and control-nonretention groups based on the retention status of mandibular second molars. Radiographic analysis was carried out to determine inclination of mandibular molars and the resulting movement of second molar centroids. Parametric and nonparametric tests were performed to assess the changes between T1 and T2. Results No statistically significant differences in molar inclination were observed between groups and timepoints (P > 0.05). There were no statistically significant differences in molar movement percentages (P > 0.05) irrespective of whether fixed retention had been used or not. Conclusions No significant eruption occurred in unopposed mandibular second molars bonded with fixed sectional retainers compared to molars partially occluded with the antagonists without fixed retention. Given the study limitations, fixed retention should be considered with caution in restricting tooth overeruption in unopposed molars.